Generation of patient‐derived tumor xenografts from percutaneous tumor biopsies in children with bone sarcomas. Issue 4 (11th December 2018) - Rainusso, Nino; Cleveland, Heather; Hernandez, J. Alberto; Quintanilla, Norma M.; Hicks, John; Vasudevan, Sanjeev; Marco, Rex A. W.; Allen‐Rhoades, Wendy; Wang, Lisa L.; Yustein, Jason T.
Abstract: One of the limitations of performing percutaneous biopsies in patients with bone sarcomas is the small amount of tumor that can be obtained for research purposes. Here, we describe our experience developing patient‐derived tumor xenografts (PDXs) using percutaneous tumor biopsies in children with bone sarcomas. We generated 14 bone sarcoma PDXs from percutaneous tumor biopsies. We also developed eight bone sarcoma PDXs from surgical resection of primary bone tumors and pulmonary metastases. A multidisciplinary team approach was critical to establish an accurate diagnosis and to provide adequate tumor samples for PDX generation.